Racial and Ethnic Differences in Genomic Profiling of Early Onset Colorectal Cancer. (2nd February 2022) - Hein, David M; Deng, Weiye; Bleile, MaryLena; Kazmi, Syed Ali; Rhead, Brooke; De La Vega, Francisco M; Jones, Amy L; Kainthla, Radhika; Jiang, Wen; Cantarel, Brandi; Sanford, Nina N
Abstract: The incidence and mortality of early onset colorectal cancer (EOCRC) is rising; outcomes appear to differ by race and ethnicity. We aimed to assess differences in mutational landscape and gene expression of EOCRC by racial and ethnic groups (non-Hispanic Asian, non-Hispanic Black, non-Hispanic White, White Hispanic) using data from the American Association for Cancer Research Project GENIE (10.2) and University of Texas Southwestern, the latter enriched in Hispanic patients. All statistical tests were 2-sided. Of 1752 EOCRC patients, non-Hispanic Black patients had higher rates of KRAS mutations (60.9%; P = .001, q = 0.015), and non-Hispanic White and non-Hispanic Black patients had higher rates of APC mutations (77.1% and 76.6% among non-Hispanic White and non-Hispanic Black patients, respectively; P = .001, q = 0.015) via the Fisher exact test with Benjamini-Hochberg correction. Using R packages DESeq2 and clusterProfiler, we found that White Hispanic patients had increased expression of genes involved in oxidative phosphorylation ( P < .001, q = 0.025). Genomic profiling has the potential to identify novel diagnostics and influence individualized treatment options to address the currently limited prognosis of EOCRC.